Використання AR-технологій при виявленні БПЛА - Крамський, І. А.; Олейніков, В. М. (ХНУРЕ, 2022)
The use of augmented reality is a promising direction in the modern world. AR can be applied in various fields of science and technology. Also, for the convenience of displaying various objects in space, you can use AR elements. The ability to see an unmanned aerial vehicle in real time somewhere in the sky on a computer monitor or other display device can speed up the process of locating the drone and eliminating it.